2023
DOI: 10.3389/fcvm.2022.1081934
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet therapy in patients with myocardial infarction with non-obstructive coronary arteries: A clinical perspective

Abstract: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous group of diseases with different pathological mechanisms, and it is uncertain whether the classical secondary prevention and treatment strategies for myocardial infarction in obstructive coronary artery disease (MI-CAD) are appropriate for patients with MINOCA. Therefore the choice of antiplatelet agents and the therapeutic effect may vary depending on the etiology and pathophysiological mechanisms of MINOCA. This requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, the efficacy of various antiplatelet therapy regimens for preventing MACCEs in individuals with nonobstructive coronary artery disease remains unclear. 14 According to existing evidence, dual antiplatelet therapy (DAPT) was not significantly better than aspirin alone in lowering 1-year MACCEs in different cardiovascular risk patients with NOCAD. [15][16][17][18] The same results were found in our recent cohort study of secondary prevention DAPT (aspirin plus the P2Y12 receptor antagonist clopidogrel) was not significantly better than aspirin alone in lowering 1-year MACCEs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of various antiplatelet therapy regimens for preventing MACCEs in individuals with nonobstructive coronary artery disease remains unclear. 14 According to existing evidence, dual antiplatelet therapy (DAPT) was not significantly better than aspirin alone in lowering 1-year MACCEs in different cardiovascular risk patients with NOCAD. [15][16][17][18] The same results were found in our recent cohort study of secondary prevention DAPT (aspirin plus the P2Y12 receptor antagonist clopidogrel) was not significantly better than aspirin alone in lowering 1-year MACCEs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of different antiplatelet treatment regimens and secondary prevention strategies for patients with non-obstructive coronary artery disease is still uncertain. 11 Lindahl B et al reported a neutral benefit for dual antiplatelet therapy in patients with myocardial infarction with non-obstructive coronary artery (MINOCA) disease. 12 The ongoing multicenter, prospective, randomized, controlled, and open-label registry-based trial MINOCA-BAT will be answering the question about the usefulness of DAPT in MINOCA patients.…”
Section: Introductionmentioning
confidence: 99%